Red and golden tomato administration improves fat diet-induced hepatic steatosis in rats by modulating HNF4α, Lepr, and GK expression - Pipitone, Rosaria Maria; Zito, Rossella; Gambino, Giuditta; Di Maria, Gabriele; Javed, Ayesha; Lupo, Giulia; Giglia, Giuseppe; Sardo, Pierangelo; Ferraro, Giuseppe; Rappa, Francesca; Carlisi, Daniela; Di Majo, Danila; et al. (Frontiers in Nutrition, 2023)
Introduction Nonalcoholic fatty liver disease (NAFLD), characterized by lipid accumulation within hepatocytes exceeding 5% of liver weight, is strongly related to metabolic disorders, obesity, and diabetes and represents a health emergency worldwide. There is no standard therapy available for NAFLD. Lifestyle intervention, including phytonutrient intake, is key in preventing NAFLD development and progression. Methods We used a rat model of NAFLD to evaluate the effect of dietary supplementation with red tomato (RT) and golden tomato (GT)—a patented mix of fruit with varying degrees of ripeness and particularly rich in naringenin and chlorogenic acid—after steatosis development. We assessed the effects on body weight, metabolic profile, and hepatic steatosis. Results and discussion We found a correlation between the amelioration of all the parameters and the liver gene expression. Our results showed that, together with the reversion of steatosis, the consumption of RT and GT can cause a significant reduction in triglycerides, low-density lipoprotein-cholesterol, fasting glucose, and homeostasis model assessment index. Meanwhile, we observed an increase in high-density lipoprotein-cholesterol according to the amelioration of the general lipidic profile. Regarding hepatic gene expression, we found the upregulation of Gk and Hnf4α involved in metabolic homeostasis, Lepr involved in adipokine signaling, and Il6 and Tnf involved in inflammatory response. Taken together, our results suggest that dietary intake of red and golden tomatoes, as a nutraceutical approach, has potential in preventing and therapeutics of NAFLD.